Exploring ecosystemic business models - Anna-Greta Nyström; Seppo Leminen (International Telecommunications Society (ITS), 2023)
Ecosystems are organizational collectives combining forces to create value offerings to a defined audience. These organizations, or firms, are linked to each other in processes of cooperation and competition simultaneously. Firms increasingly choose an ecosystem strategy over other alternatives to ensure value co-creation and capture (Hannah & Eisenhardt, 2018). Subsequently, ecosystem strategy enables a context in which the firm can build, leverage, and extend, as opposed to merely locating and occupying a strong position (Autio and Thomas, 2018). An ecosystem is essentially a network of organizations (suppliers, distributors, producers, government agencies, NGOs etc.) involved in the production or delivery of a product, service, or solution. A business ecosystem is characterized by a certain degree of dependence for the ecosystem to function. Research has identified ecosystem offerings as malleable and users as having a broader range of opportunities to define the value offering (e.g., customization) compared to the context of conventional supply chains (cf. Autio, 2022). Ecosystems have less hierarchical arrangements and more independent participants, which pose challenges of orchestration. For example, ecosystem partners should behave in such a way that they contribute to an increased value of the focal participant's offering, but the question of how to persuade ecosystems partners to do so remains, especially if there are less hierarchical arrangements (e.g., licensing agreements, predefined roles). Ecosystem orchestration, in turn, is linked to the value offering that the ecosystem collectively produces, which inevitably arises from the participating firms' business models. (...)
Keywords: 330